Mitochondrial quality control and transfer communication in neurological disorders and neuroinflammation - Ma, Yinrui; Song, Rui; Duan, Chenyang (Frontiers in Immunology, 2025)
Mitochondria, as the primary energy factories of cells, play a pivotal role in maintaining nervous system function and regulating inflammatory responses. The balance of mitochondrial quality control is critical for neuronal health, and disruptions in this balance are often implicated in the pathogenesis of various neurological disorders. Mitochondrial dysfunction not only exacerbates energy deficits but also triggers neuroinflammation through the release of damage-associated molecular patterns (DAMPs), such as mitochondrial DNA (mtDNA) and reactive oxygen species (ROS). This review examines the mechanisms and recent advancements in mitochondrial quality control in neurological diseases, focusing on processes such as mitochondrial fusion and fission, mitophagy, biogenesis, and protein expression regulation. It further explores the role of mitochondrial dysfunction and subsequent inflammatory cascades in conditions such as ischemic and hemorrhagic stroke, neurodegenerative diseases and brain tumors. Additionally, emerging research highlights the significance of mitochondrial transfer mechanisms, particularly intercellular transfer between neurons and glial cells, as a potential strategy for mitigating inflammation and promoting cellular repair. This review provides insights into the molecular underpinnings of neuroinflammatory pathologies while underscoring the translational potential of targeting mitochondrial quality control for therapeutic development.